Analisis Swot Untuk Menentukan Strategi Kompetitif Pada Pd. Bpr. Bank Daerah Lamongan - Mohammad Rizal Nur Irawan (Fakultas Ekonomi Universitas Kadiri, 2017)
The rising of global competition, the companies must considering the circumstances of market and more competitiveof determine strategy. Competitive strategy is a way to determine the power competitiveness. Use of an effective SWOT analysis for a role in determining the competitive strategy, in order to determine the strengths, weaknesses, opportunities and threats encountered by company to keep going company survive. The Problems which you want to find the answer in this study is